Estimation of Dysbetalipoproteinemia Incidence in Iraqi Patients with Diabetes Mellitus and Cardiovascular Disease - Samar T. Hameed, Qasim S. Al-Mayah, Mahmood S. Khudhair, Ghassan A. Al-Shamma (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The main obvious manifestations in dysbetalipiproteinemia (DBL) are Apo-B, non-high-density lipoprotein cholesterol (non-HDLc) and Apo-E gene polymorphism, with a remarkable controversy in the results among different workers. The aim of the study was to find a suitable variable or formula for diagnosis of familial or secondary DBL in a sample of Iraqi patients with type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). Material and methods: The study involved 50 patients with T2DM (mean age 46.48 ±9.3 years), 26 patients with CVD (mean age: 43.15±7.34 years) and 73 apparently healthy normal control individuals (mean age: 34.51±11.47 years) with almost equal male/female ratio. Serum lipids (TC, TG, HDL-c, LDL-c, VLDL-c, Remnant like particles RLP, Apo-B, and Apo-E) were estimated in patients and controls. The receiver operating characteristic (ROC) curve was used to evaluate the diagnostic value of non-HDL-c and non-HDL-c /Apo-B in the context of discrimination between patients with- and without DBL. Results: All measured serum lipids, were higher in patients than controls, except HDL-c. Using Sniderman algorithm, 13 patients (18.06%) among T2DM and CVD were considered to have DBL, while none of control group had this disorder. Conclusion Based on Sniderman algorithm, ROC revealed a better specificity and sensitivity for non- HDLc to diagnose DBL,